CORE COMPETENCIES OF BANCASSURANCE SALES MANAGERS IN INDONESIA: A CASE STUDY OF THE BANCASSURANCE CHANNELThe life insurance industry in Indonesia faces increasingly complex growth challenges, particularly in the bancassurance channel, which operates under - Ariesta Handoko Pratama; Dedy Sushandoyo (CV. Radja Publika, 2026)
The life insurance industry in Indonesia faces increasingly complex growth challenges, particularly in the bancassurance channel, which operates under high target pressure, and with dependence on the quality of collaboration between insurance and banking companies. Under these conditions, the role of the Bancassurance Sales Manager (BSM) are responsible for achieving sales targets, managing teams, maintaining business relationships, and ensuring the effectiveness of field activities. This study aims to identify the core competencies of high-performing BSMs in Indonesia using a sequential exploratory mixed-method approach. The first stage was conducted through in-depth interviews with six high-performing BSMs. The second stage consisted of a survey of 38 respondents using a questionnaire based on Hersey and Blanchard's situational leadership. The results identified four core competencies of high-performing BSMs : (1) situational leadership, (2) business relationship, (3) adaptive team management, and (4) time management. The quantitative findings showed the dominance of S1 and S3 leadership styles as well as significant correlations in sales coaching and team meeting activities. These findings confirm that BSM effectiveness is determined by the ability to adapt in leading, build strategic business relationships, manage teams flexibly, and regulate time in a disciplined manner according to the demands of the bancassurance business.